Workplace holistic health and wellness: a healthy move towards Viksit Bharat Abhiyan 2047 - Kumar, Santosh; Prasad, Boby; Nayak, Chitranshi; Aastha, (International Journal Of Community Medicine And Public Health, 2025)
Lifestyle diseases, such as diabetes, cardiovascular diseases, obesity, and hypertension, are witnessing a rapid increase across India. This surge is largely attributed to modern sedentary lifestyles, poor dietary practices, inadequate physical activity, and high levels of occupational and personal stress. These conditions not only compromise individual health and quality of life but also significantly impact workplace productivity, increase absenteeism, and burden the healthcare system. In response to this growing challenge, organizations in India are progressively adopting workplace holistic health and wellness programs. These initiatives go beyond conventional health check-ups and address the physical, mental, emotional, and social dimensions of employee well-being. They include interventions such as yoga and mindfulness sessions, nutritional guidance, regular health screenings, mental health counselling, physical activity promotion, and stress management workshops. This study explores the evolution and growing relevance of workplace wellness programs in the Indian context. It analyses the critical components that make these initiatives effective and highlights their measurable impact on reducing the burden of lifestyle diseases. Furthermore, it emphasizes the role of a holistic and preventive health approach in fostering a healthier, more productive workforce. The integration of wellness into the workplace not only benefits individual employees but also contributes to national development goals by enhancing human capital. As India moves towards the realization of the Viksit Bharat Abhiyan a vision of a developed and progressive nation. By promoting employee well-being, these initiatives align closely with the broader goals of sustainable economic growth, social welfare, and national prosperity.